Exploration the Gastronomic Characteristics of Traditional Dishes in Tuban Regency, East Java, Indonesia - Andriani, Riska; Kurniahu, Hesti; Rahmawati, Annisa (El-Hayah:Jurnal Biologi, 2024)
Traditional dishes are part of cultural preservation and serve as a regional identity. Therefore, research is needed on traditional dishes, specifically the traditional dishes of Tuban, with a focus on ethnobiology and culinary culture, taste, nutritional aspects, and health. This study aims to explore and analyze the traditional dishes of Tuban from a gastronomic perspective, to provide guidance on the presentation and consumption of these dishes to ensure they do not negatively impact health, thus contributing to the welfare and preservation of traditional cuisine. This research is qualitative in nature, aiming to examine the diversity of dishes and their ingredients, traditional processing methods and technologies used, cultural enculturation, taste, historical and traditional elements, as well as the perceptions and appreciation of local communities in Tuban Regency, East Java Province, towards traditional dishes. The data sources include the local Tuban community, tourists, traditional dish makers from Tuban, academics, and information from other researchers. The research objects are traditional Tuban dishes. The results indicate that there are 27 main types of ingredients characteristic of Tuban's traditional dishes, which consist of both animal and plant sources. Preparation methods before processing these key ingredients traditionally include fermentation, boiling, pounding, slicing, smoking, and drying. The processing methods for Tuban's traditional dishes are fermentation, boiling, steaming, frying, and sautéing. Traditional technologies used in processing these dishes include bumbung for tapping and fermenting palm sap and hirik for clay smoking in making ampo snacks. The dominant flavors of Tuban's traditional dishes are sweet, sour, salty, spicy, and savory.